Two new species of the genus Broscosoma Rosenhauer, 1846 (Coleoptera, Carabidae, Broscinae) from China - Jiang, Ri-Xin; Feng, Qi; Wang, Shuo (Zootaxa, 2020)
Two new species of the genus Broscosoma Rosenhauer, 1846 (Carabidae: Broscinae) were found in China: Broscosoma xuhaoi sp. nov. from Chongqing City and Broscosoma zhengyuandongi sp. nov. from Fujian Province. Habitus and diagnostic features of the new species are described and illustrated. An updated list of all known Chinese Broscosoma species is given.